Pengaruh Pemeriksaan dan Penagihan Pajak Terhadap Kepatuhan Wajib Pajak dengan Informasi Tren Media sebagai Variabel Moderating (Studi Kasus KPP Pratama Jakarta Kebayoran Baru Tiga) - Devy Yekti Palupi; Eva Herianti (Universitas Trunojoyo Madura, 2017)
This research is motivated by the influence of the examination and collections of taxes on tax compliance are already widely carried out by the tax authorities in each LTO. This study aims to explain the extent to which the tax assessment and billing is done fiskus (KPP Pratama Jakarta Kebayoran Baru Tiga) affect taxpayer compliance and the extent to which information media trends contribute in terms of disseminating information on taxation to the taxpayer and to make trend this medium as a variable moderating. This research is quantitative and data collection techniques used were a questionnaire. The research result is said to be significant because a positive result 0.50 were declared invalid, and therefore the study found that: 1) Tax assessment has positive and significant effect of the information media trends, 2) tax billing has positive and significant effect of the information media trends, 3) information media trends has positive and significant impacton tax compliance, 4) tax audit has positive effect and significant impact on tax payer compliance, and 5) tax collection has positive significant effect on the corporate tax payers